Sensing Chiral Drugs by Using CdSe/ZnS Nanoparticles Capped with N‐Acetyl‐L‐Cysteine Methyl Ester. Issue 33 (28th June 2013) - Delgado‐Pérez, Teresa; Bouchet, Lydia M.; de la Guardia, Miguel; Galian, Raquel E.; Pérez‐Prieto, Julia
Abstract Chiral quantum dots (QDs), differing in their core or shell size and, consequently, in their optical properties, were synthesized by the treatment of commercially available amine‐capped quantum dots with methyl ester N‐acetyl‐L‐cysteine (CysP). Interestingly, their colloidal methanol solutions remain stable for several months. Their NMR and IR spectra were in accordance with CysP binding to the QD surface through two anchoring groups; its thiolate (strongly bound) and the carbonyl group of its ester (weaker bound) group, whereas their circular dichroism (CD) spectra showed a new broad redshifted band, suggesting that the attachment to the QD surface modified the conformational equilibrium towards conformer(s) with optical activity in this region. These QDs were sufficiently fluorescent to perform studies of the chiral recognition of drugs, in particular the aryl propionic acids (APAs) ketoprofen (KP), naproxen (NP), flurbiprofen (FP), and ibuprofen (IP). We used different drug concentration ranges, depending on the QD solubility. All the assayed drugs quenched the QD emission in a concentration‐dependent mode. Quenching fluorescence assays with the chiral QDs (CS@CysP) showed their extraordinary capacity for the chiral recognition of KP, NP, and FP, and particularly in the case of KP and FP, a remarkable positive allosteric effect was detected for the R enantiomer. By using a drug/CS@CysP molar ratio of 5000:1 and 2500:1, the changes of intensity and the sign of the CD spectrum of the drug evidenced the dissociation of the drug carboxylic group in the presence of the QD.